Sensors Variety for UAVs Swarms Modeling and Simulation Purposes – cPSOm Algorithm Use Case - Stanisław SKRZYPECKI; Zbigniew TARAPATA; Dariusz PIERZCHAŁA (Communications of International Proceedings, 2021)
In this paper considerations of further researches in modeling and simulation of Unmanned Aerial Vehicles (UAVs) swarms are presented. This considerations concern listing and description variety of sensors assembled in aircrafts and its possible impact and capabilities when applied in specific modification of particle swarm optimization (PSO) algorithm. The algorithm, called combined PSO methods (cPSOm), is used for a search problem in a large-scale terrain and has been enhanced with collision avoidance, leadership or formation arrangement features. Furthermore, analysis of applying these sensors in original distributed simulation environment with multiagent and multiresolution modelling possibility is performed. Finally, the consideration leads to conclusion that the approach will have a positive effect in making simple experiments reflected the real life scenarios.
Keywords: UAVs sensors; PSO algorithm; UAVs swarm; modelling and simulation